Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Distinct impaired patterns of intrinsic functional network centrality in patients with early- and late-onset Alzheimer’s disease - Jiong Zhou; Kaicheng Li; Xiao Luo; Qingze Zeng; Yerfan Jiaerken; Shuyue Wang; Xiaopei Xu; Xiaocao Liu; Zheyu Li; Tianyi Zhang; Yanv Fu; Shuai Zhao; et al. (Brain Imaging and Behavior, 2021)